(untitled) (International Journal of Environmental Sciences, 2025)
Background: A group of diseases affecting both humans and animals, leishmaniasis is caused by the protozoan parasite Leishmania, which is a member of the Trypanosomatidae family. Iraq is among the countries with the highest prevalence of visceral leishmaniasis (VL). The study aimed to investigate the biochemical and histological effect on kidney and spleen of male albino rats infected with Leishmania donovani. Methodology: 20 rats were divided into 4 groups (n=5): G1 and G3 regarded as control administrated distilled water for 30 and 60 days respectively and G2 and G4 infected by (2x107) parasites/ rat for 30 and 60 days respectively. The animals were sacrificed at 31 and 61 day post infection (Pi.). Results: The results showed that there was no significant change in means of total protein, globulin and albumin levels in male albino rats treated with parasite for 30 days and 60 days. Histological data of kidney showed focal glomerular atrophy and revealed hyaline cast in the renal tubule in rats treated with parasite for 30 days, as compared with control group. While the histological section of kidney in male rats treated with parasite for 60 days showed normal architecture of tissue as compared with control group. Spleen section revealed white pulp atrophy, secondary lymphoid follicles with blurring of the boundaries between white pulp and red pulp in rats treated for 30 days, on the other hand there was blurring of the boundaries between white and red pulp in rats treated for 60 days. Conclusion: L.donovani causes several changes in tissue form (kidney an spleen) including focal glomerular atrophy and revealed hyaline cast in the renal tubule in kidney and white pulp atrophy, secondary lymphoid follicles with blurring of the boundaries between white pulp and red pulp in spleen and its function in the host.